Perbedaan Perilaku Ibu Menyusui Sebelum dan Sesudah Penerapan Model Promosi Kesehatan Berbasis Social Learning Theory - Amalia, Chindy Kana; Prijatni, Ida; Restanty, Dian Aby (Poltekkes Kemenkes Malang & IBI Ranting Pendidikan Kota Malang, 2023)
Correct breastfeeding technique is a way of giving breast milk to babies with the correct attachment and breastfeeding position. From the results of a preliminary study conducted on ten breastfeeding mothers in the Balung Public Health Center Work Area, it was found that six breastfeeding mothers were wrong in their attachment and seven were wrong in their breastfeeding position. With health promotion based on social learning theory, breastfeeding mothers' behavior can be improved by emphasizing the need for conditioning and imitation. This study aims to determine differences in the behavior of breastfeeding mothers before and after the implementation of social learning theory-based health promotion in the Balung Public Health Center Work Area. This study was a pre-experimental study with a one group pre and post test design. The population of this study used mothers who had babies aged 0-6 months in the Working Area of the Balung Health Center as many as 54 people with a purposive sampling technique, namely 35 respondents. Data collection using a questionnaire. Data analysis with the Wilcoxon Signed Ranks Test. There are differences in breastfeeding behavior before and after the implementation of social learning theory-based health promotion in the Balung Public Health Center Work Area, with an Asymp value. Sig. (2-tailed) = 0.000 < 0.05. Differences in the behavior of breastfeeding mothers after being given health promotion based on social learning theory can occur because providing information about breastfeeding techniques can increase the knowledge, skills, and motivation of mothers regarding breastfeeding.